THE ROLE AND ACTIVITIES OF THE NURSE IN THE SPREAD AND PREVENTION OF INFECTIOUS DISEASES AMONG THE TEAM (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article provides a comprehensive analysis of the critical role that nurses play in preventing the spread of infectious diseases within healthcare teams. It examines the nature of infectious disease transmission in clinical settings, the nurse’s role in education and practice, the implementation of infection control protocols, and collaborative measures with interdisciplinary teams. The study draws on existing literature, primary research findings, and best practices to propose actionable strategies for strengthening the nurse’s contribution to infection prevention.